ANALYSIS OF THE IMPACT OF MERGERS AND ACQUISITIONS ON THE VALUE OF FINANCIAL SYNERGY - Sarpi, Sarpi; Rizkianto, Eko (Dynamic Management Journal, 2024)
This study analyzes how mergers and acquisitions affect financial synergy in Indonesian public and state-owned companies. Using metrics like profitability, efficiency, liquidity, solvency, and funding capacity, it examines one year before and five years after these transactions, based on data from 84 firms (2005-2015, financial reports spanning 2004-2020). The Wilcoxon signed rank test calculates pre- and post-merger averages. Findings show decreased capital costs (debt, equity, weighted average) but also reduced profitability (ROIC) and efficiency (TAT). Stakeholders should focus on enhancing financial synergy by boosting funding capacity and planning to improve profitability, efficiency, solvency, and liquidity. Future research should specifically measure the incremental financial synergy value post-transaction and the value generated from operational synergy.